Гідравлічний розрахунок водопровідної мережі з активними елементами - Сафоненко, В. В. (ХНУРЕ, 2024)
The problem of hydraulic calculation of water supply networks with active elements consists in solving the system of equations of the steady-state flowdistribution model when flow and pressure measurements are given at the network inlets and outlets. The model of steady-state flow distribution for passive and active sections of the water supply network is given. A mathematical model of steady-state flow distribution for a water supply network of complex structure is formulated. The formulation of the problem of hydraulic calculation is given for the case when pressure values are set at all inputs and outputs of the network.
Keywords: модель сталого потокорозподілу; гідравлічний розрахунок водопроводної мережі